Consolidated bioprocessing performance of a two‐species microbial consortium for butanol production from lignocellulosic biomass - Jiang, Yujia; Lv, Yang; Wu, Ruofan; Lu, Jiasheng; Dong, Weiliang; Zhou, Jie; Zhang, Wenming; Xin, Fengxue; Jiang, Min (Biotechnology and bioengineering, 2020)
Consolidated bioprocessing (CBP) by using microbial consortium was considered as a promising approach to achieve direct biofuel production from lignocellulose. In this study, the interaction mechanism of microbial consortium consisting of Thermoanaerobacterium thermosaccharolyticum M5 and Clostridium acetobutylicum NJ4 was analyzed, which could achieve efficient butanol production from xylan through CBP. Strain M5 possesses efficient xylan degradation capability, as 19.73 g/L of xylose was accumulated within 50 hr. The efficient xylose utilization capability of partner strain NJ4 could relieve the substrate inhibition to hydrolytic enzymes of xylanase and xylosidase secreted by strain M5. In addition, the earlier solventogenesis of strain NJ4 was observed due to the existence of butyrate generated by strain M5. The mutual interaction of these two strains finally gave 13.28 g/L of butanol from 70 g/L of xylan after process optimization, representing a relatively high butanol production from hemicellulose. Moreover, 7.61 g/L of butanol was generated from untreated corncob via CBP. This successfully constructed microbial consortium exhibits efficient cooperation performance on butanol production from lignocellulose, which could provide a platform for the emerging butanol production from lignocellulose. Microbial consortia could perform more complicated tasks through the labor division. An emerging constructed two‐species consortium consisting of lignocellulosic degrader strain M5 and butanol producer strain NJ4 showed complementary functions, and the interaction mechanism of microbial consortium was explored through the analysis of key genes transcriptional levels. Finally, 13.28 g/L of butanol was obtained from xylan, and 7.61 g/L of butanol was achieved from corncob via CBP after the fermentation optimization. The successful microbial consortium could provide the platform for the emerging butanol production from lignocellulose.